THE EFFECTOF WORK LIFE QUALITY, WORK CULTURE, WORK MOTIVATION, AND RELIGIUSITY ON STAFFS PERFORMANCE - Nury Yasien Rachmatullah; Muhaimin Dimyati; Zainollah Zainollah (MBA - Journal of Management and Business Aplication, 2019)
This empirical investigation aimed to determine the effectof  work life quality, work culture, work  motivation,  and  religiusity  on  the staffsperformance in  SD  Al  BaitulAmien  (full  day school)  Jember.  Population  of  this  study  was  all  tachers  in    SD  Al  BaitulAmien  (full  day school)  Jembertotaling  20  persons  used  for  the  sample.Data  were  collected  with  a questionnaireusing a Likert scale. Then theywere analyzed using correlation and regressiontechniques using Statistical  Package  For  Social  Science  (SPSS)program version23.0.The study found that : 1) Quality of working life (QWL) has a positive effect onthe performance of  staffs  in  the  SD  Al  BaitulAmien  (full  day  school)  Jember.  2)  theworkmotivation  has  a positive  effect  onthe  staffsperformance  in  the  SD  Al  BaitulAmien  (full  day  school) Jember.3) Work culturehaspositive effect on staff performance in SD Al BaitulAmien (full day  school)  Jember.  4) Religiosity  have  a  positive  effect  on  staff  performance  in  SD  AlBaitulAmien (full day school) Jember. The findings of this study provide practical advice to staffs  and  principals  to  be  able to enhance  SD  Al  BaitulAmien  (full  day  school)  Jember. Quality  of  working  life,  work  culture,  motivation  and  religiosity  in  orderto  optimize  the performance of staff increased at SD Al BaitulAmien (full day school) Jember.